Improving Viewing Ability In Narrative Text Using the Picture and Picture Method - Marfuatin Nafi'ah; Sulistyaningsih Sulistyaningsih (South Sulawesi Education Development (SSED), 2024)
This classroom action research aims to improve mastery of English viewing skills at junior high school level, especially in class 8F MTsN 2 Sidoarjo by including learning activities based on the fun Picture and Picture method so that students' results or grades increase. This was done because in class 8F MTsN 2 Sidoarjo, the results of students' mastery of English viewing skills seemed low. 32 eighth-grade students participated in the study. Another reason why researchers took viewing skills is because viewing is a new skill in the Merdeka Curriculum. This research uses a type of classroom action research that begins with a pre-cycle and is divided into two cycles, each cycle perfecting learning with the fun Picture and Picture method based on insights from the previous cycle. The methodology includes initial tests, learning based on the Picture and Picture method, observation, and assessment. Results showed continuous improvement, with scores increasing with each cycle. Observations prove the characteristic of teaching using this method, namely that students are freer to express their opinions about an object. The implications of this research suggest that teachers use interesting methods because their success is measured better than using conventional methods. This research states that with 2 cycles learning success reaches 97%.